2017
DOI: 10.1002/wcc.468
|View full text |Cite
|
Sign up to set email alerts
|

Heat, health, and humidity in Australia's monsoon tropics: a critical review of the problematization of ‘heat’ in a changing climate

Abstract: Exposure to heat has killed more people in Australia than all other natural hazards combined. As the climate warms, temperatures are projected to rise substantially, increasing the impact of heat stress and heat illness nation-wide. The relation between heat and health is profoundly complex, however, and is understood differently across multiple sectors. This paper thus provides a critical review of how heat is currently measured and managed in Australia, highlighting how humidity, exposure, and exertion are k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 96 publications
(181 reference statements)
2
22
1
Order By: Relevance
“…We would have expected that respondents from the cooler regions (e.g., Tasmania) would be less likely to be often heat stressed than those in hotter jurisdictions such as Queensland and the Northern Territory. Even when the locations where people lived were separated into the tropical parts of northern Australia, characterized by high temperatures throughout the year and high humidity during large parts of the year (wet season), and southern Australia, we could detect no significant difference in level of heat stress, contrary to expectations [ 40 ]. Only one control variable, self-reported health, had a significant ( p < 0.001) impact on respondents’ heat stress levels with those in better health less likely to say they were often or very often heat stressed than those in poorer health.…”
Section: Discussioncontrasting
confidence: 98%
“…We would have expected that respondents from the cooler regions (e.g., Tasmania) would be less likely to be often heat stressed than those in hotter jurisdictions such as Queensland and the Northern Territory. Even when the locations where people lived were separated into the tropical parts of northern Australia, characterized by high temperatures throughout the year and high humidity during large parts of the year (wet season), and southern Australia, we could detect no significant difference in level of heat stress, contrary to expectations [ 40 ]. Only one control variable, self-reported health, had a significant ( p < 0.001) impact on respondents’ heat stress levels with those in better health less likely to say they were often or very often heat stressed than those in poorer health.…”
Section: Discussioncontrasting
confidence: 98%
“…Most notably our findings agree with Guichard (2014), Oueslati et al (2017) and Sambou et al (2020) on the leading role of greenhouse effect of moisture during Sahelian nighttime heatwaves. It should be noted that this process is not specific to the Sahel but is also observed during nighttime heatwaves over other tropical regions (e.g Oppermann et al 2017;Chen et al 2019). Likewise, the shortwave radiation at the southernmost part of the Sahel accompanying daytime heatwaves corroborates the findings of (Oueslati et al 2017) and is also found to drive some heatwaves in midlatitude areas like Europe (e.g Lhotka et al 2018).…”
Section: Discussionsupporting
confidence: 69%
“…While the temperate zone follows a pattern of summer/autumn/winter/spring, the tropical Australian north follows a wet/dry seasonality, and Cairns has an average yearly rainfall of almost 2,000 mm that falls mainly between November and April. The rain differential in Cairns is 1:8 rather than 1:3 in more temperate areas, which encourages unique water management practices and produces a 'hydrological' seasonality with a distinctive kind of tropical 'heat' (Oppermann et al, 2017). Rain comes in heavy downpours during months that are also very hot (an average of 32°C).…”
Section: The Backyard As Hydrological Spacementioning
confidence: 99%